Mineral Resource Assessment in Complex Ore Deposits based on International Standards - Battalgazy, Nurassyl; Madani, Nasser (The Complex Orebodies conference, 2018)
Geostatistical simulation has been widely used in mineral resource classification of metalliferous deposits based on international standards such as JORC code. However, the modeling process becomes challenging whenever the relationship among the variables of interest are complicated and cumbersome to model. This characteristic sometimes manifest itself in complex spatial and global cross-correlation measures, deeply depending on the formation and genesis of the deposit. The objective is then to generate the models that not only reproduces this significant characteristics, but also, it leads to better understanding of a mineral resource estimation and successive decision-makings. In this respect, there are different approaches taking into account the spatial correlation structures, for which it can be classified as independent simulation, co-simulation and factor-based methodologies....
Keywords: geostatistical simulation; mineral resource